(untitled) (CIPEEX, 2025)
FindBus is a web application created to improve the experience of public transport users in Anápolis. The system uses geolocation technologies (GPS) to provide real-time data on bus locations, allowing users to track routes and estimated arrival times directly on an interactive map. The backend will be implemented in Python due to its simplicity, efficiency, and extensive tool library for integrating geolocation and data analysis systems. The frontend will be developed with HTML, CSS, JavaScript, and other web technologies, focusing on a light and intuitive user interface. The project will adhere to IT governance practices aligned with ITIL and COBIT to ensure security, reliability, and scalability, supporting high traffic during peak hours. If successful, FindBus will expand to include a mobile app and cover bus routes from the terminal and neighboring cities. Development will be phased, with monitoring through KPIs and real-time dashboards using Power BI.